Property in human body parts - Goold, I (Edward Elgar Publishing, 2024)
The expanding uses of body parts in biomedicine and elsewhere has created new thinking on how we might understand the legal status of human biomaterials. This chapter examines why the question of whether property concepts apply to body parts has emerged, focusing on the numerous examples of judicial decisions in which property-based thinking has created a new way of regulating body parts, although not without giving rise to considerable debate in both the courts and scholarship. It also engages with the question of whether the law should treat human body parts as property, critically evaluating why and how the courts drew on property law concepts in addressing these challenges. It concludes by arguing the resort to property law principles is indicative of deeper lacunae in the law and in medical ethics which have created challenges and have left the courts reeling for solutions to difficult questions about who may use human biomaterials and how.